A redshift survey of herschel far-infrared selected starbursts and implications for obscured star formation - Casey, C.; Berta, S.; Béthermin, M.; Bock, J.; Bridge, C.; Budynkiewicz, J.; Burgarella, D.; Chapin, E.; Chapman, S.; Clements, D.; Conley, A.; Conselice, C.; et al. (2012)
We present Keck spectroscopic observations and redshifts for a sample of 767 Herschel-SPIRE selected galaxies (HSGs) at 250, 350, and 500 μm, taken with the Keck I Low Resolution Imaging Spectrometer and the Keck II DEep Imaging Multi-Object Spectrograph. The redshift distribution of these SPIRE sources from the Herschel Multitiered Extragalactic Survey peaks at z = 0.85, with 731 sources at z < 2 and a tail of sources out to z ~ 5. We measure more significant disagreement between photometric and spectroscopic redshifts ( Δz/(1 + z spec) = 0.29) than is seen in non-infrared selected samples, likely due to enhanced star formation rates and dust obscuration in infrared-selected galaxies. The infrared data are used to directly measure integrated infrared luminosities and dust temperatures independent of radio or 24 μm flux densities. By probing the dust spectral energy distribution (SED) at its peak, we estimate that the vast majority (72%-83%) of z < 2 Herschel-selected galaxies would drop out of traditional submillimeter surveys at 0.85-1 mm. We find that dust temperature traces infrared luminosity, due in part to the SPIRE wavelength selection biases, and partially from physical effects.As a result, we measure no significant trend in SPIRE color with redshift; if dust temperature were independent of luminosity or redshift, a trend in SPIRE color would be expected. Composite infrared SEDs are constructed as a function of infrared luminosity, showing the increase in dust temperature with luminosity, and subtle change in near-infrared and mid-infrared spectral properties. Moderate evolution in the far-infrared (FIR)/radio correlation is measured for this partially radio-selected sample, with q IR∝(1 + z)–0.30 ± 0.02 at z < 2. We estimate the luminosity function and implied star formation rate density contribution of HSGs at z < 1.6 and find overall agreement with work based on 24 μm extrapolations of the LIRG, ULIRG, and total infrared contributions. This work significantly increased the number of spectroscopically confirmed infrared-luminous galaxies at z 0 and demonstrates the growing importance of dusty starbursts for galaxy evolution studies and the build-up of stellar mass throughout cosmic time.